Cultural discourses in the ten Hiligaynon short stories of Maria Luisa Defante-Gibraltar. - Borja, Mary Joy Sanoson (2006)
Literature touches emotions, changes and guides thoughts and moves the reader towards a fruitful and progressive life. A certain society, race, or nation is determined by its culture. Culture is also determined by the literature, music, art, including artifacts and written documents, as well as the material culture of that given society. Literature is life-it is the fountain of life for every human person. Reading literature is a very beautiful experience for everybody because it can take you to the places you have never been before. Definitely, short stories often express realities in life that are made into one exciting piece of literature. These short stories are often based on experience of every person in his undertaking with everyday life. These experiences are crucial to his development and may either affect other person.
Thesis (Undergraduate, Bachelor of Arts in Literature/History) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Gibraltar, Maria Luisa Defante; Cultural discourses -- Hiligaynon short stories; Short Stories -- Hiligaynon